Ecofisiologia foliar de melastomataceae dos campos rupestres - Silvana Aparecida Barbosa de Castro (2015)
Numerous processes drive the evolution of functional traits of leaves of plant species of Campos Rupestres plant species, which are characterized by enormous species richness and endemism. We evaluated the evolution of leaf functional traits of leaves related to the efficiency of capturing light, water economy and the conservation of resources of 30 species of Melastomataceae of xeric and mesic habitats from campos rupestres. We hypothesized that environmental filters and competitive interactions are responsible for the evolution of the functional traits of leaves of the studied species, and we expect to find phylogenetic signal in closely related species indicating possible niche conservatism. Among the leaf traits evaluated were leaf area, specific leaf area, length of petiole, thickness of mesophyll and stomatal density. We used the method of phylogenetic independent contrasts and decomposition of diversity among nodes to evaluate leaf characteristics in a phylogenetic context. We observed a clear separation between endemic and widely distributed species, and differences between species of mesic and xeric habitats. We also found numerous convergences, especially in Microlicieae and Melastomeae, while divergences were observed in Miconieae. We believe that the convergences in leaf characteristics are a result of the action of environmental filters while divergences are due to competitive interactions, especially in species located in mesic habitats. We observed phylogenetic signal for the majority of evaluated traits, suggesting niche conservation throughout the evolution of Melastomataceae. The decomposition of diversity among the nodes revealed greater diversity in the direction of the root of the tree, especially the node where Miconieae diverges from Melastomeae and Microlicieae. The possibility of niche conservation as a function of phylogenetic signal in the species evaluated can be crucial in the current scenario of climate change, since these species of campos rupestres may not be sufficiently labile to adapt to rapid environmental changes.